Hydrothermal Co-liquefaction of Cellulose and Polypropylene using Co-solvents - Danam Mahesh; S. Harisankar; Rajnish Kumar; R. Vinu (Energy Nexus)
Hydrothermal co-liquefaction of feedstocks that decompose in widely different temperature regimes is a promising strategy to convert thermally stable olefinic plastics at sub-critical conditions by utilizing the synergetic interactions between the intermediates generated from biopolymers and synthetic polymers. In this study, cellulose and polypropylene (PP) are co-liquefied, and the effects of temperature (300–350 °C), residence time (15–45 min), cellulose-to-PP mass ratio (25:75, 50:50 and 75:25 w%/w%) and co-solvents (glycerol, paraffin oil) on product yields and quality are thoroughly studied. Results suggest that water alone is inadequate to liquefy PP, while the incorporation of glycerol and paraffin oil greatly enhance the conversion and the bio-crude yield. Maximum bio-crude yield (78.6 wt.%) was obtained at 350 °C-30 min with cellulose:PP of 50:50 w%/w% using water:glycerol solvent. The selectivity to aliphatic hydrocarbons in the bio-crude was high (∼96.5 %) at 350 °C-15 min for a cellulose:PP ratio of 25:75 w%/w% in water-paraffin oil solvent.